Implementasi Penerapan Undang-Undang Nomor 13 Tahun 2006 tentang Perlindungan Saksi dan Korban (Sudi di Polres Kuningan) - Haris Budiman; Gios Adhyaksa (Universitas Kuningan, 2015)
Article 1 (1) of the 1945 Constitution states that, Indonesia is the law of the State in the form of Republic. Therefore, the provisions of the applicable legislation and set the life of the Indonesian nation comes from the law, whether written or unwritten law. One runway is used as basic guidelines in order to achieve justice for all Indonesian people, especially in the field of law, set forth in Article 27 paragraph (1) of the Act of 1945, which reads,